Posttreatment MR findings in spinal dural arteriovenous malformations. - Willinsky, R A; terBrugge, K; Montanera, W; Mikulis, D; Wallace, M C (American Journal of Neuroradiology, 1995)
PURPOSE To review the MR findings in 17 patients with spinal dural arteriovenous malformations and compare posttreatment MR with clinical outcome in 10 patients. METHODS Extramedullary flow voids, cord swelling, and intramedullary signal changes were recorded in 17 patients. Enhancement and vessel cospicuity were assessed in 10 patients given gadopentetate dimeglumine. In 10 patients, follow-up MR was correlated with clinical outcome. RESULTS Of the 17 patients, 14 (82%) had abnormal subarachnoid vessels, 11 (65%) had cord enlargement, and 16 (94%) had hyperintensity on T2-weighted images. In 3 patients, the vessels were better seen with contrast, and 6 had cord enhancement. On posttreatment MR, the vessels were no longer evident in 7 of 10 patients, cord swelling resolved in 9 of 9 patients, the the T2 hyperintensity resolved or was less evident in 9 of 9 patients. Eight patients had clinical improvement, and 2 stabilized. CONCLUSIONS Follow-up MR showed resolution of most of the findings in spinal dural arteriovenous malformation. There was some correlation between MR and clinical outcome, but MR evaluation could not distinguish those who had improved from those who stabilized.